Kepemimpinan Transformasional dan Kinerja Karyawan dengan Mediasi Efikasi Diri Kreatif pada Perusahaan di Sektor Jasa Kurir, Logistik, dan Transaksi Keuangan di Indonesia - R Rina Novianty Ariawaty; Hilmiana Hilmiana; Muhammad Syauqi Taufiqur Rahman (Society, 2025)
In an organization, individual performance greatly influences organizational performance through activities driven by individuals or groups working together, who play an active role in producing strong organizational outcomes. The success of an organization in achieving its established goals depends largely on the extent to which leadership is effectively exercised. One aspect leaders must pay attention to in improving employee performance is employees’ level of creative self-efficacy. Companies operating in the courier services, logistics, and financial transactions sectors are transforming in terms of business processes, human resources, subsidiary strengthening, and product development. However, they also face very intense competition from similar companies such as JNE, J&T, Tiki, SiCepat, and Ninja Express. This study aims to analyze and determine the effect of transformational leadership on employee performance through creative self-efficacy in companies within the courier services, logistics, and financial transactions sectors in Indonesia. The research employs descriptive and verification methods, using SmartPLS 3.3.3 as the analytical tool and collecting data through questionnaires. The sampling method applied is convenience sampling. The results and conclusions of this study indicate that transformational leadership has a positive and significant effect on employee performance. Transformational leadership also has a positive and significant effect on creative self-efficacy. Furthermore, creative self-efficacy positively and significantly affects employee performance. Finally, transformational leadership has a significant indirect effect on employee performance through creative self-efficacy.